THE INTEGRATION OF DUOLINGO INTO EFL LEARNING - Ira Irzawati (Esteem Journal of English Education Study Programme, 2023)
This study seeks to present an overview of the positive effects of incorporating Duolingo into English as a Foreign Language (EFL) learning. Through a review of fifteen journal articles sourced from reputable online databases, the researcher analyzed the effectiveness of using Duolingo in EFL learning. The findings indicated that integrating Duolingo into EFL learning had several benefits, including improved mastery of grammar and vocabulary, enhanced listening, reading, speaking, and writing skills, and increased student motivation to learn. The results of this study provide valuable and comprehensive information regarding the positive impacts of incorporating Duolingo into EFL learning. Such information is not commonly presented in similar research, which often focuses on investigating the use of Duolingo to improve specific English skills or components. This research aims to contribute to the development of EFL research by offering new insights into the integration of Duolingo into EFL learning.